2012
DOI: 10.1186/1471-2431-12-152
|View full text |Cite
|
Sign up to set email alerts
|

Reducing stress and supporting positive relations in families of young children with type 1 diabetes: A randomized controlled study for evaluating the effects of the DELFIN parenting program

Abstract: BackgroundTo assess initial efficacy and feasibility of a structured behavioural group training (DELFIN) for parents of children with diabetes type 1, in order to reduce parenting stress and to improve parenting skills.MethodsA randomized controlled study was conducted between July 2008 and September 2010, at a children’s hospital in Hannover with parents of children with type 1 diabetes (2–10 yrs) (intervention group n = 37; control group n = 28). Parenting skills, parents’ psychological burden, children’s be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 38 publications
2
66
0
5
Order By: Relevance
“…Behavioural parenting interventions are recognised as best practice in the treatment of parenting and child behaviour difficulties (O'Connell, Boat, & Warner, 2009), however these have rarely been applied in the context of child illness management (Kirk et al, 2012). Recent studies have demonstrated some positive, albeit mixed, effects of parenting intervention for child chronic conditions (Clarke, Calam, Morawska, & Sanders, 2014;Doherty, Calam, & Sanders, 2013;Lohan, Morawska, & Mitchell, 2015;Sassmann, de Hair, Danne, & Lange, 2012;Westrupp, Northam, Lee, Scratch, & Cameron, 2015) providing promising signs that this approach may add value to existing health services.…”
Section: Introductionmentioning
confidence: 94%
“…Behavioural parenting interventions are recognised as best practice in the treatment of parenting and child behaviour difficulties (O'Connell, Boat, & Warner, 2009), however these have rarely been applied in the context of child illness management (Kirk et al, 2012). Recent studies have demonstrated some positive, albeit mixed, effects of parenting intervention for child chronic conditions (Clarke, Calam, Morawska, & Sanders, 2014;Doherty, Calam, & Sanders, 2013;Lohan, Morawska, & Mitchell, 2015;Sassmann, de Hair, Danne, & Lange, 2012;Westrupp, Northam, Lee, Scratch, & Cameron, 2015) providing promising signs that this approach may add value to existing health services.…”
Section: Introductionmentioning
confidence: 94%
“…Since this is a descriptive analysis it cannot be concluded that there is a level of significance. Some research work has been done about psychosomatic issues in the diabetic population [7] [8]. The perception of certain details of the patients' first stay in hospital has not been analyzed so far.…”
Section: Discussionmentioning
confidence: 99%
“…Parental support and a warm and understanding attitude towards the child have a positive effect on the child's diabetes self-care. Reducing stress among the parents has had encouraging results in improving the interaction between parents and child [6]. Some support has been found for parenting skills training, especially among children with T1DM and behavioral problems [7].…”
Section: Introductionmentioning
confidence: 99%